Comparative study of biodiesel from Jatropha and orange peel oils as pilot fuels in a dual-fuel engine. Issue 23 (1st December 2016) - Kumar, Parvesh; Kumar, Naveen
ABSTRACT: The diesel-like properties of biodiesel make it a good alternative for CI engines. In the present work, the scope of biodiesel as a pilot fuel has been studied and compared with diesel. The results show that the use of Jatropha oil methyl ester (JOME) and orange peel oil methyl ester (OPOME) as pilot fuel improves BTE and BSFC of dual-fuel engines compared to diesel as a pilot fuel. The use of JOME and OPOME as a pilot fuel for CNG also decreases the emissions like unburnt hydrocarbons, CO, and smoke. However, NO X emissions increase at higher load. In contrast, use of biodiesel as pilot fuel improves the performance and emissions characteristics of dual-fuel engines.